Enhancing tour guides’ professional competence through precise and effective English communication skills for improved tourist engagement and service quality - Ni Putu Lovyta Mai Yoren; Ni Putu Somawati; Erly Wahyuni (Journal of Language, Literature, Social and Cultural Studies, 2026)
This study aims to examine how precise and effective English communication enhances tour guides’ professional competence, tourist engagement, and overall service quality. The research adopts a mixed-method approach involving quantitative surveys and qualitative interviews with professional tour guides and international tourists in major tourism destinations. Data were collected through structured questionnaires, observation checklists, and semi-structured interviews to capture both performance indicators and experiential insights. The analysis employs descriptive statistics and regression analysis to identify the relationship between English communication proficiency and service outcomes, while thematic analysis is used to interpret qualitative responses. The findings indicate that tour guides with higher levels of linguistic accuracy, clarity, and intercultural communication skills significantly improve tourist satisfaction, trust, and engagement. Furthermore, effective communication reduces misunderstandings and enhances the overall travel experience. The study concludes that strengthening English communication through targeted training programs is essential for improving tour guides’ professionalism and competitiveness in the global tourism industry. It recommends continuous language development, practical communication training, and the integration of cultural awareness into professional development initiatives.